PERKEMBANGAN PENELITIAN PENDOKUMENTASIAN PENGETAHUAN ADAT TERHADAP LINGKUNGAN BERKELANJUTAN: ANALISIS BIBLIOMETRIK DI SCOPUS (2017-2022) - Amwa, Muhammad Yusrizal; Salim, Tamara Andriani; Datang, Frans Asisi (Jurnal Perpustakaan dan Informasi, 2024)
This study evaluated recent scientific publication trends related to documenting indigenous knowledge about the environment using a bibliometric technique. The investigation used keywords such as "environmental," "indigenous knowledge," "traditional knowledge," and "documentation" to identify 91 scientific papers, which were then narrowed down to 37 studies published in the last five years and written in English. Using VOSviewer software, a bibliometric study resulted in the identification of three major clusters: "Indigenous Knowledge," "Medical Plant," and "Ethnobotany." The findings revealed that these studies are most commonly undertaken in the United States, followed by India, China, and Indonesia. These results provide a better understanding of the current state of research; countries actively engaged in indigenous knowledge documentation, and potential future research directions in the context of indigenous knowledge, which is crucial to addressing global environmental concerns and achieving sustainability.